A new method for estimating the free-to-adsorbed ratio in shale gas reservoirs using acoustic amplitude attenuation and porosity. (30th June 2017) - Liu, Kun; Sun, Jianmeng; Gu, Ming; Liu, Haitao; Chen, Xiangyang
Abstract: Free and adsorbed gas content are the key parameters for estimating the volume of initially in-place shale gas. Due to the difficulty of accurately obtaining water saturation and pore pressure in shale gas reservoirs, as well as other drawbacks, a new method is proposed to estimate the free-to-adsorbed ratio based on the acoustic amplitude attenuation coefficient and porosity. Moreover, a joint experiment of the adsorption isotherm and acoustic amplitude measurement is carried out to study the main factors influencing the free-to-adsorbed ratio. Firstly, the experimental operation process was designed; then, the relationship between pore space and net pressure was studied. After that, the adsorbed and free gas content were calculated. Secondly, the amplitude obtained by the fast Fourier transform (FFT) was compared with the amplitude obtained from the root mean square (RMS) approach. Then, the acoustic amplitude attenuation coefficient was estimated in order to study the relationship between the free-to-adsorbed ratio, acoustic amplitude attenuation coefficient as well as porosity. Thirdly, according to the experimental data, the empirical formula of the free-to-adsorbed ratio was acquired and was successfully applied to estimate the free-to-adsorbed ratio in shale gas reservoirs in the YS area. Finally, with satisfying accuracy, the practical applications were found to be in good agreement with the results of the traditional methods, which proves the reliability of the introduced method.